2021
DOI: 10.3390/cancers13225731
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Liquid Biopsy in Endometrial Cancer

Abstract: Background: Liquid biopsy is a minimally invasive collection of a patient body fluid sample. In oncology, they offer several advantages compared to traditional tissue biopsies. However, the potential of this method in endometrial cancer (EC) remains poorly explored. We studied the utility of tumor educated platelets (TEPs) and circulating tumor DNA (ctDNA) for preoperative EC diagnosis, including histology determination. Methods: TEPs from 295 subjects (53 EC patients, 38 patients with benign gynecologic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The dataset GSE156902 [ 8 , 24 ] contained cohorts of asymptomatic controls, multiple sclerosis patients, selected as a group of patients with a non-malignant disease with a significant inflammatory component, and patients with different forms of cancer. GSE158508 [ 3 ] contained cases of ovarian cancer patients, GSE184904 included endometrial cancer patients [ 21 ], and GSE89843 included non-small cell lung cancer (NSCLC) patients [ 15 ]. The dataset of sarcoma was previously published [ 25 ].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset GSE156902 [ 8 , 24 ] contained cohorts of asymptomatic controls, multiple sclerosis patients, selected as a group of patients with a non-malignant disease with a significant inflammatory component, and patients with different forms of cancer. GSE158508 [ 3 ] contained cases of ovarian cancer patients, GSE184904 included endometrial cancer patients [ 21 ], and GSE89843 included non-small cell lung cancer (NSCLC) patients [ 15 ]. The dataset of sarcoma was previously published [ 25 ].…”
Section: Datamentioning
confidence: 99%
“…We also studied the utility of tumor-educated platelets and circulating tumor DNA for preoperative endometrial cancer diagnosis, including histology determination. We provided evidence that liquid biopsy can complement, if not replace, standard microscopic traditional biopsy evaluation [ 21 ]. The aforementioned studies lay the groundwork for a novel approach to liquid biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Two years later in 2017, Best et al showed high accuracy of detecting early- (81%) and late-stage (88%) of NSCLC using TEP transcriptome profiles, independent of age, smoking habit, whole-blood storage time and various inflammatory conditions ( 89 ). In a liquid biopsy study of endometrial cancer, the accuracies of utilizing TEP transcriptome profiles and circulating tumor DNA (ctDNA) coupled with artificial intelligence were compared and the authors reported higher accuracy and AUC of TEP-dedicated classifier in predicting endometrial cancer ( 90 ). Xu et al reported that TEP RNA profiles have high potential of distinguishing and staging CRC patients from other noncancerous intestinal diseases ( 91 ).…”
Section: Clinical Applications Of Platelets For Cancer Patientsmentioning
confidence: 99%
“…[ 79 , 119 , 129 ] To avoid overestimating the diagnostic value, in addition to healthy donors, the control group should include suspected cases, such as the precursor stage of cancer, benign disease, and inflammatory cases, from which malignant disease is more difficult to discriminate. [ 10 , 139 ] Moreover, sex, age, obesity, smoking status, etc might affect the platelet RNA profile and should be properly matched with the experimental groups. [ 87 , 98 , 140 , 141 ] Furthermore, researchers found that the performance of platelet RNAs was not desirable in differentiating breast cancer from other cancers, suggesting that the inclusion of patients with other cancers is necessary to improve Sp during the screening phase.…”
Section: Platelet Rnas Are Informative On the Cancer Diagnostics Journeymentioning
confidence: 99%